Thrombopoietin receptor agonists for acquired thrombocytopenia following anti-CD19 CAR-T-cell therapy: a case report. Issue 7 (16th July 2021) - Baur, Rebecca; Jitschin, Regina; Kharboutli, Soraya; Stoll, Andrej; Völkl, Simon; Büttner-Herold, Maike; Schmidt, Daniela; Rösler, Wolf; Mackensen, Andreas; Mougiakakos, Dimitrios
Abstract : Chimeric antigen receptor (CAR)-modified T-cells targeting CD19 represent a promising therapy for relapsed or refractory (r/r) lymphoma and leukemia. The most common adverse events are immune related and include cytokine release syndrome and neurotoxicity. However, early and late hematological toxicity has emerged as a substantial clinical hurdle leading among others to an increased risk for infections or bleeding. The underlying pathophysiology remains elusive and supportive measures comprise stem cell support or the use of growth factors. Here, we report a 66-year-old woman with r/r diffuse large B-cell lymphoma that received anti-CD19 CAR-T-cells achieving a complete metabolic remission. At month 3 after adoptive cell transfer, the patient still exhibited a grade 3 anemia and a grade 4 thrombocytopenia. The latter required regular platelet transfusions. Bone marrow smear revealed hypocellularity without dysplasia. Despite reduced megakaryopoiesis, immature platelet fraction was elevated indicating an at least partially consumptive underlying component. Based on the successful use of Romiplostim, a thrombopoietin receptor-agonist, in aplastic anemia and immune thrombocytopenia, we treated our patient accordingly. Platelet count (and hemoglobin levels) increased and the patient remains transfusion-free. Taken together, our therapeutic approach could represent a novel strategy for managing CAR-T-cell-related hematotoxicity but, self-evidently, requires further controlled clinical studies.